Multimodal reflection for creative facilitators: an approach to improving self-care. Issue 6 (1st November 2016) - Moffatt, Amanda; Barton, Georgina; Ryan, Mary
Abstract: Creative and arts-based facilitators who work in the area of supporting others, such as youth workers, educators, counsellors and therapists, often do not prioritise their own well-being and self-care. This paper explores a study that focused on the utility of multimodal reflection for sustainable as well as satisfying practice for creative facilitators. Participants in the study were involved in a trial 10-week reflective programme called Stepping Outside the Circle. This programme was part of a larger research project that sought to understand the professional and reflective practices of creative facilitators, a term used within the study to encompass practitioners who use arts (both performative and visual) interventions to work within a variety of therapeutic and educational settings. During the programme, participants drew on their own personal knowledge of the disciplines in which they worked and reflected in and on this practice both professionally and personally. They also collaboratively supported each other through the process. We argue that engagement in multimodal reflection shared with others, particularly for creative facilitators, is integral for purposeful and effective self-care practice.